A microworld-based role-playing game development approach to engaging students in interactive, enjoyable, and effective mathematics learning. Issue 3 (3rd April 2018) - Wang, Sheng-Yuan; Chang, Shao-Chen; Hwang, Gwo-Jen; Chen, Pei-Ying
ABSTRACT: In traditional teacher-centered mathematics instruction, students might show low learning motivation owing to the lack of applied contexts. Game-based learning has been recognized as a potential approach to addressing this issue; however, without proper alignment between the gaming and math-applied contexts, the benefits of game-based learning could be limited. Therefore, this study aims to develop a microworld-based educational game, which provides simulated contexts encouraging students to explore, discover, and solve practical problems using the mathematics knowledge gained in the class. A quasi-experimental design was implemented in the learning activity of the "Speedy World" unit in an elementary school mathematics course to examine the effectiveness of the proposed approach. A total of 107 sixth graders participated in the experiment. The experimental results showed that the students who learned with the microworld-based gaming approach had better learning achievement and motivation in the mathematics course than those who learned with the conventional technology-enhanced learning approach. In addition, the students also showed that they highly accepted the microworld-based game for learning mathematics. The findings of this study provide good evidence for the importance and necessity of associating authentic applied contexts with gaming contexts in developing computer educational games for mathematics.